Forecasting national activity using lots of international predictors: an application to New Zealand - Sandra Eickmeier; Tim Ng (Deutsche Bundesbank, 2009)
We look at how large international datasets can improve forecasts of national activity. We use the case of New Zealand, an archetypal small open economy. We apply "data-rich" factor and shrinkage methods to tackle the problem of efficiently handling hundreds of predictor data series from many countries. The methods covered are principal components, targeted predictors, weighted principal components, partial least squares, elastic net and ridge regression. Using these methods, we assess the marginal predictive content of international data for New Zealand GDP growth. We find that exploiting a large number of international predictors can improve forecasts of our target variable, compared to more traditional models based on small datasets. This is in spite of New Zealand survey data capturing a substantial proportion of the predictive information in the international data. The largest forecasting accuracy gains from including international predictors are at longer forecast horizons. The forecasting performance achievable with the data-rich methods differs widely, with shrinkage methods and partial least squares performing best. We also assess the type of international data that contains the most predictive information for New Zealand growth over our sample.
Keywords: 330; Forecasting; factor models; shrinkage methods; principal components; targeted predictors; weighted principal components; partial least squares; Konjunkturprognose; Prognoseverfahren; Faktorenanalyse; Hauptkomponentenanalyse; Neuseeland; Konjunkturindikator; Welt